Repair effect of neurotrophic factor III (NT-3) on rats with spinal injury model and its mechanism: NT-3 repair mechanism in rat spinal injury - Zou, Dexin; Wang, Huimin; Hao, Sibin; Chen, Feng (Cellular and Molecular Biology, 2024)
The present study aimed to study the repair effect of neurotrophic factor III (NT-3) on spinal injury model rats and its mechanism. Wistar rats with spinal injury were established by accelerated compression stroke after the operation and divided into control group, model group, and NT-3 intervention group. The motor function of rats in each group was evaluated at different postoperative time points (3, 7, 14 d). HE staining was used to detect the changes in tissue structure and morphology of the injured spinal column in each group. The changes of SOD, MDA and GSH in serum of rats were detected. The concentrations of inflammatory cytokines IL-1β, IL-6, IL-17 and TNF-α in serum were detected by enzyme-linked immunosorbent assay (ELISA). Western blot was used to detect the expression changes of anti-apoptotic protein (Bcl-2) and pro-apoptotic protein (Bax) in injured spinal tissue of rats in each group. Compared with model group, motor function score of NT-3 intervention group increased gradually, and had statistical significance at 7 and 14 days (5.29±1.62 vs 9.33±2.16, 5.92±1.44 vs 14.56±2.45, T =7.386, 9.294, P =0.004, 0.000). The levels of SOD and GSH in serum of NT-3 intervention group were significantly increased (t=9.117, 12.207, P=0.000, 0.000), while the level of MDA was significantly decreased (t=5.089, P=0.011). Serum levels of inflammatory cytokines IL-1β, IL-6, IL-17 and TNF-α in NT-3 intervention group were significantly decreased (T =6.157, 7.958, 6.339, 6.288, P=0.008, 0.005, 0.005, 0.007). In the NT-3 treatment group, Bax protein was significantly decreased (0.24±0.05 vs 0.89±0.12, T =8.579, P=0.001), and the relative expression of Bcl-2 protein was significantly increased (0.75±0.06 vs 0.13±0.05, T =9.367, P=0.001). Neurotrophic factor III can promote spinal injury repair in spinal injury model rats, and play a role by enhancing antioxidant stress ability, inhibiting inflammatory factors, promoting Bcl-2 and decreasing Bax expression.